THE RELATIONSHIP BETWEEN MOTHERS' KNOWLEDGE, ATTITUDES, AND BEHAVIOR TOWARDS THE IMPORTANCE OF BASIC IMMUNIZATION - Wada, Fauziah H; Sunirah, Sunirah; Sari, Dinda Permata; Mara Imbang Satriawan Hasiolan (Nursing Genius Journal, 2025)
Background: Basic immunization is one of the most effective public health interventions to prevent infectious diseases and reduce morbidity and mortality among infants and young children. Despite the availability of immunization services, coverage rates in several regions of Indonesia have declined in recent years, indicating persistent challenges in immunization uptake. Maternal factors, particularly knowledge, attitudes, and behavior, play a crucial role in decision-making regarding childhood immunization. Inadequate knowledge, negative attitudes, and vaccine hesitancy among mothers may contribute to incomplete immunization, even when health services are accessible. Purpose: To analyze the relationship between mothers’ knowledge, attitudes, and behaviors regarding the importance of basic immunization for infants. Methods: This study employed a quantitative cross-sectional design conducted at the Integrated Health Post (Posyandu) RT 002, Karangsatria Subdistrict, Bekasi Regency, Indonesia. Total of 117 respondents were selected using purposive sampling based on predefined inclusion criteria.  Data were analyzed using bivariate analysis using the chi-square test to examine relationships between variables. Ethical approval was obtained from the Ethics Committee of Bani Saleh Health College (No: EC.200/KEPK/STKBS/VII/2024). Results:  Bivariate analysis revealed a statistically significant relationship between maternal knowledge and attitudes toward basic immunization (p = 0.008). However, no significant relationship was found between maternal knowledge and immunization behavior (p = 0.060), nor between maternal attitudes and immunization behavior (p = 0.348). Conclusion:  Maternal knowledge was significantly associated with attitudes toward basic immunization, whereas neither knowledge nor attitudes were significantly associated with immunization behavior, indicating that immunization practices are influenced by factors beyond individual cognition and attitudes.